2021
DOI: 10.3390/rel13010034
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Religion in Secular Healthcare: Existential Communication and the Post-Secular Negotiation

Abstract: This article aims to understand why religion has proven difficult to address in secular healthcare, although existential communication is important for patients’ health and wellbeing. Two qualitative data samples exploring existential communication in secular healthcare were analyzed following Interpretative Phenomenological Analysis, leading to the development of the analytical constructs of ‘the secular’ and ‘the non-secular’. The differentiation of the secular and the non-secular as different spheres for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
5
0
3
Order By: Relevance
“…In contemporary Denmark, in what has been called a post-secular context, the representation of religion and spirituality is heterogeneous. 19 Around 75 per cent of Danes are members of the national Evangelical Lutheran Protestant Church, while only 2 per cent attend religious services weekly. Faith is considered a societal taboo, second only to mental disorders in magnitude.…”
Section: Religion and Spirituality In Post-secular Denmarkmentioning
confidence: 99%
See 1 more Smart Citation
“…In contemporary Denmark, in what has been called a post-secular context, the representation of religion and spirituality is heterogeneous. 19 Around 75 per cent of Danes are members of the national Evangelical Lutheran Protestant Church, while only 2 per cent attend religious services weekly. Faith is considered a societal taboo, second only to mental disorders in magnitude.…”
Section: Religion and Spirituality In Post-secular Denmarkmentioning
confidence: 99%
“…10 At the same time, a multitude of religious and spiritual orientations are now readily available and practised at different levels of society. 11 In addition, a growing body of quantitative epidemiological evidence suggests a robust protective effect of religious and spiritual activity and community on most health outcomes, including those relating to physical, mental and social health. 12 In a recent study published in The Lancet Regional Health -Europe, Stripp and colleagues found that as many as 81.9 per cent of Danes reported a strong or very strong existential or spiritual need during the previous month.…”
mentioning
confidence: 99%
“…Herfra privatiseres også eksistentiel taenkning -det vaere sig spirituel, religiøs eller sekulariseret eksistentiel taenkning (Hvidt et al, 2021;la Cour & Hvidt, 2010). Dette post-sekulaere perspektiv giver mulighed for en forståelse, hvor tilstedevaerelsen af spirituelle, religiøse og eksistentielle temaer, tanker, ressourcer og behov i mennesket anerkendes, vaerdsaettes og bringes i fokus i den sekulaere samfundsdiskurs og i sundhedsvaesenet isaer (Nissen & Andersen, 2022). I vores konceptualisering af åndelig omsorg fokuserer vi på spirituelle, religiøse og / eller sekulaere eksistentielle orienteringer, behov og ressourcer, i forbindelse med livstruende sygdom og krise (Hvidt et al, 2018;Hvidt et al, 2020;Ramezani et al, 2014).…”
Section: åNdelig Omsorg Fra Et Post-sekulaert Perspektivunclassified
“…Vi forstår det post-sekulaere som erkendelsen af, at den klassiske sekulariseringsteori, som haevdede at religion ville forsvinde i takt med oplysning og modernitet vandt frem, ikke er et holdbart grundlag for at forstå religiøsitet i en globaliseret verden (Beaumont et al, 2020;Berger, 2014;Gauthier, 2019). Det kommer til udtryk i en bred samfundsbaseret holdningsaendring i forhold til religioners fortsatte tilstedevaerelse i det offentlige rum, og forsøget på at forhandle denne tilstedevaerelse i multikulturelle og pluralistiske kontekster, herunder også det stigende fokus på åndelig omsorg i det danske sundhedsvaesen og (Berger, 2015;Gorski, 2012;Habermas, 2008;Nissen & Andersen, 2022;Nynäs, 2012). I sundhedsvaesenet kan det post-sekulaere ses i den nu udbredte konsensus blandt politikere, forskere, praktikere og patienter om, at integration af åndelig omsorg på alle niveauer af de sundhedsfaglige indsatser er gavnlig for patienter, og anbefales af såvel forskere og WHO (Jones et al, 2021;Puchalski et al, 2009;World Health, 2014).…”
unclassified
“…Spiritual support within healthcare has had a long and distinguished history (Swift, 2014 ). Steeped within religious traditions, western healthcare has been systematically uncoupling from these traditions in keeping with growing secularism within the context of modern societies (Nissen et al, 2021 ). However, healthcare chaplaincy and pastoral care services, which arose from this legacy, remain intrinsic to the provision of healthcare across societies at large, for the simple reason that people require this support.…”
Section: Introductionmentioning
confidence: 99%